Analisis Kinerja Guru berdasarkan Faktor Eksternal di SMP Negeri Kecamatan Trienggadeng Kabupaten Pidie Jaya - Novi, Noviani; Kamaruddin, Kamaruddin (Aceh Cooperative Care, 2023)
This study aims to analyze external factors, namely the principal's leadership, organizational culture and the application of School-Based Management to improving teacher performance. This research is in the form of a survey using a correlational method with a quantitative approach. The problem analysis tool to answer this problem uses path analysis techniques and primary data collection techniques through closed questionnaires on the research object, namely 91 teachers of public junior high schools in Trienggadeng District, Pidie Jaya Regency. So that the researchers found that from the results of the data analysis it was proven: (1) There was a direct and indirect influence of the principal's leadership on teacher performance of 45.27%, (2) There was a direct and indirect influence of the principal's leadership on teacher performance. culture on teacher performance by 42.72%, (3) There is a direct and indirect influence of school-based management on teacher performance by 34.35%, (4) Simultaneously school-based leadership, organizational culture and school-based management contribute to increased performance teachers in Trienggadeng District Public Middle School, Pidie Jaya Regency by 51.4%.